Advanced film‐forming gel formula vs spring thermal water and white petrolatum as primary dressings after full‐face ablative fractional CO2 laser resurfacing: a comparative split‐face pilot study. (4th August 2017) - Marini, L.
Abstract: Background: Aesthetically pleasing results and fast, uneventful recovery are highly desirable after rejuvenating ablative laser procedures. Wound dressings following ablative laser procedures should ideally improve and optimize the wound healing environment. Objective: The purpose of this comparative split‐face, single‐blinded, prospective observational study was to assess the efficacy and acceptability of two primary wound dressings immediately after a full‐face fractional CO2 laser resurfacing procedure. Methods: The assessments of an innovative film‐forming dressing called Stratacel (SC) vs spring thermal water + Vaseline (V+) were conducted after a standardized, single‐pass, full‐face ablative fractional CO2 laser skin resurfacing procedure. Clinical parameters, such as haemoglobin – HB; surface temperature – ST; micro‐textural modifications – MT; superficial melanin – M; intrafollicular porphyrins – P, were assessed at different phases of the healing process using standardized, non‐invasive technologies. Results: Five female volunteers were enrolled in this inpatient, controlled pilot study. Most of the clinical parameters considered, including 3D surface texture analysis, revealed a better performance of SC vs. V+ during the early, more delicate phases of the healing process. Conclusions: This preliminary study, even if performed on a small number of volunteers, confirmed a definite advantage of the tested semipermeable film‐forming formula (SC) over a more conventional postoperative skin care regime (V+). Clinical results could be explained by a better uniformity of distribution of SC over the micro‐irregularities induced by ablative fractional CO2 laser resurfacing. Its thin, semipermeable film might, in fact, act as an efficient, perfectly biocompatible, full contact, temporary skin barrier, able to protect extremely delicate healing surfaces from potential environmental irritations.